Physical models have gender‐specific effects on student understanding of protein structure–function relationships. Issue 4 (29th February 2016) - Forbes‐Lorman, Robin M.; Harris, Michelle A.; Chang, Wesley S.; Dent, Erik W.; Nordheim, Erik V.; Franzen, Margaret A.
Abstract: Understanding how basic structural units influence function is identified as a foundational/core concept for undergraduate biological and biochemical literacy. It is essential for students to understand this concept at all size scales, but it is often more difficult for students to understand structure–function relationships at the molecular level, which they cannot as effectively visualize. Students need to develop accurate, 3‐dimensional mental models of biomolecules to understand how biomolecular structure affects cellular functions at the molecular level, yet most traditional curricular tools such as textbooks include only 2‐dimensional representations. We used a controlled, backward design approach to investigate how hand‐held physical molecular model use affected students' ability to logically predict structure–function relationships. Brief (one class period) physical model use increased quiz score for females, whereas there was no significant increase in score for males using physical models. Females also self‐reported higher learning gains in their understanding of context‐specific protein function. Gender differences in spatial visualization may explain the gender‐specific benefits of physical model use observed. © 2016 The Authors Biochemistry and Molecular Biology Education published by Wiley Periodicals, Inc. on behalf of International Union of Biochemistry and Molecular Biology, 44(4):326–335, 2016.